A Comparative Study of the Financial Assistance for the Subscription of Shares in terms of the 1973 and 2008 Companies Acts - Delport, Petrus Albertus (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.